2017
DOI: 10.1016/j.jaci.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Follicular helper T cells mediate IgE antibody response to airborne allergens

Abstract: Background Type 2 helper T (Th2) cells have long been believed to play a pivotal role in allergic immune responses, including IgE antibody production and type 2 cytokine-mediated inflammation and pathology. A new T cell subset, T follicular helper cells (Tfh) cells, is specialized in supporting B cell maturation and antibody production. Objective To investigate the roles of Tfh cells in allergic immune responses. Methods Naïve mice were exposed to cytokines or natural allergens through the airways. Develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
145
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(153 citation statements)
references
References 62 publications
7
145
0
1
Order By: Relevance
“…Follicular helper T (Tfh) cells are distinguished from other CD4 + T cells by their selective role in orchestrating germinal center responses and in promoting the development of memory B cells and long‐lived plasma cells . Recent findings suggested that IL‐33 was also involved in the development of Tfh cells . Indeed, airway administration of IL‐33 together with OVA antigen induced IL‐4 expression in two distinct CD4 + T‐cell subsets, CD4 + ST2 + CXCR5 − Th2 cells and CD4 + ST2 − CXCR5 + Tfh cells, in lung draining lymph nodes .…”
Section: Il‐33 In Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Follicular helper T (Tfh) cells are distinguished from other CD4 + T cells by their selective role in orchestrating germinal center responses and in promoting the development of memory B cells and long‐lived plasma cells . Recent findings suggested that IL‐33 was also involved in the development of Tfh cells . Indeed, airway administration of IL‐33 together with OVA antigen induced IL‐4 expression in two distinct CD4 + T‐cell subsets, CD4 + ST2 + CXCR5 − Th2 cells and CD4 + ST2 − CXCR5 + Tfh cells, in lung draining lymph nodes .…”
Section: Il‐33 In Adaptive Immunitymentioning
confidence: 99%
“…Recent findings suggested that IL‐33 was also involved in the development of Tfh cells . Indeed, airway administration of IL‐33 together with OVA antigen induced IL‐4 expression in two distinct CD4 + T‐cell subsets, CD4 + ST2 + CXCR5 − Th2 cells and CD4 + ST2 − CXCR5 + Tfh cells, in lung draining lymph nodes . Adoptive transfer experiments showed that Th2 cells mediated eosinophilic airway inflammation and transient production of antigen‐specific IgE antibody, whereas the Tfh cells mediated sustained production of IgE.…”
Section: Il‐33 In Adaptive Immunitymentioning
confidence: 99%
“…Thereafter, they are thought to be an independent lineage of helper T cells, which are essential for inducing affinity maturation and isotype switching of B cells . In addition, a recent study has shown that Tfh cells play an essential role in IgE production for protein allergens . Furthermore, Tfh cells have been shown to differentiate into pathogenic Th2 cells that produce IL‐4 and IL‐13 and play a pathogenic role in asthma .…”
Section: Roles Of Other Helper T‐cell Subsets In Asthmamentioning
confidence: 99%
“…Supporting these findings of the importance of Tfh cells in directing IgE responses, a functional dichotomy between Th2 and Tfh cells in regulating peripheral inflammation and IgE, respectively, has begun to emerge. Adoptive transfer of Th2 cells led to allergic airway inflammation as evidenced by lung eosinophilia but weak IgE responses, whereas transfer of Tfh cells led to poor airway inflammation but robust IgE responses . Further, deletion of Tfh cells does not impair type 2 cellular immune responses, such as lung infiltration of eosinophils in models of allergic airway disease …”
Section: Tfh Cells As Drivers Of Ige Responsesmentioning
confidence: 99%
“…using reporters for IFNγ and IL‐4 cytokine expression, it was observed that murine B cells that interacted with IFNγ + Tfh cells made IgG2 transcripts, whereas B cells that interacted with IL‐4 + Tfh cells made IgG1 transcripts during L. major infection . Recent experiments using mice with conditional loss of Bcl6 or IL‐6 receptor signaling in T cells, which abrogates Tfh cell development, showed that Tfh cells are critical for inducing IgE in multiple type 2 responses including to allergens . Further, bone marrow chimera experiments that isolated IL‐4 deficiency to Tfh cells also demonstrated severely reduced IgE responses, suggesting that Tfh cell‐derived IL‐4 is the main driver of IgE in vivo .…”
Section: Tfh Cells As Drivers Of Ige Responsesmentioning
confidence: 99%